Growth and quality of passion fruit seedlings under salt stress and foliar application of H2O2 - Ramos, Jailton Garcia; de Lima, Vera Lucia Antunes; de Lima, Geovani Soares; Pereira, Mariana de Oliveira; da Silva, André Alisson Rodrigues; Nunes, Kheila Gomes (Comunicata Scientiae, 2022)
Passion fruit is a species with high production potential under the climatic conditions of the Brazilian Northeast region. However, water sources in this region show high salt concentrations that can compromise crop development. In this scenario, the application of small hydrogen peroxide concentrations reduces the deleterious effects caused by salt stress on the production yield of agricultural crops. From this perspective, this study aimed to evaluate the growth and quality of yellow passion fruit seedlings irrigated with saline water and foliar application of hydrogen peroxide. The experiment was conducted in a plant nursery at the Federal University of Campina Grande, PB. The experimental design was in randomized blocks in a 5 x 2 factorial. Treatments consisted of five levels of electrical conductivity of the irrigation water - ECw (0.6, 1.2, 1.8, 2.4, and 3.0 dS m-1) and two concentrations of hydrogen peroxide - H2O2 (0 and 20 μM), with four replications and two plants per plot, totaling 80 plants. The exogenous application of 20 μM hydrogen peroxide favored plant growth in stem diameter, plant height, number of leaves, and the Dickson Quality Index of the passion fruit cv. BRS Rubi do Cerrado. The application of 20 μM hydrogen peroxide induced the acclimatization of the passion fruit cv. BRS Rubi do Cerrado irrigated with saline water.